Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/gji/ggw483
|View full text |Cite
|
Sign up to set email alerts
|

Comparing gravity-based to seismic-derived lithosphere densities: a case study of the British Isles and surrounding areas

Abstract: S U M M A R YLithospheric density structure can be constructed from seismic tomography, gravity modelling, or using both data sets. The different approaches have their own uncertainties and limitations. This study aims to characterize and quantify some of the uncertainties in gravity modelling of lithosphere densities. To evaluate the gravity modelling we compare gravity-based and seismic velocity-based approaches to estimating lithosphere densities. In this study, we use a crustal model together with lithosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 61 publications
(97 reference statements)
1
28
0
Order By: Relevance
“…The general pattern is dominated by dense material beneath S-E Great Britain and the British Atlantic margin, and a low-density anomaly in Scotland, Northern Ireland and the N-W offshore domain. This feature is also present in some of the models in the gravity-tomography study of Root et al (2017). The lithospheric structure in Ireland in our M1_s model follows a pattern similar to that in Fullea et al (2014), with a moderate thinning from S to N. Elastic thickness maps (derived from thermal and seismic data at European scale) reflecting the strength of the lithosphere are rather diverse in the British Isles (e.g., Cloetingh et al, 2005;Tesauro et al, 2009a,b).…”
Section: Final Lithospheric Modelssupporting
confidence: 66%
See 2 more Smart Citations
“…The general pattern is dominated by dense material beneath S-E Great Britain and the British Atlantic margin, and a low-density anomaly in Scotland, Northern Ireland and the N-W offshore domain. This feature is also present in some of the models in the gravity-tomography study of Root et al (2017). The lithospheric structure in Ireland in our M1_s model follows a pattern similar to that in Fullea et al (2014), with a moderate thinning from S to N. Elastic thickness maps (derived from thermal and seismic data at European scale) reflecting the strength of the lithosphere are rather diverse in the British Isles (e.g., Cloetingh et al, 2005;Tesauro et al, 2009a,b).…”
Section: Final Lithospheric Modelssupporting
confidence: 66%
“…These authors modeled a moderate lithospheric thickening in the western Irish margin aligned with the ISZ. More recently Root et al (2017) have studied the mantle density structure of the British Isles and surrounding areas combining gravity data and seismic tomography models (e.g., Schaeffer and Lebedev, 2013) utilizing different crustal models: CRUST1.0 (Laske et al, 2013), EuCRUST-07 (Tesauro et al, 2008) and Kelly et al (2007).…”
Section: Geological and Geophysical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, this means that the gravitational effect of the mantle density distribution fromẑ − V to z Max can be predicted with an accuracy (1σ) better than 1.5 mGal (for the current scenario). Since Root et al [29] showed that in general, available tomographic models are filtered with a 200 km half width Gaussian filter, we evaluate the effect of the presence of high frequencies in the lithosphere by computing the gravitational signal due to random density anomalies with correlation length in the x, y directions of 50 km, an amplitude of 100 kg m −3 and a fixed thickness of 5000 m. It turns out that this perturbation to the initial model produces effects of the order of few tenths of a milligal which are therefore negligible.…”
Section: Model Volume Vmentioning
confidence: 99%
“…[9,10]). Interior models for other planets and moons in the solar system are constrained by remote sensing and geodesic data obtained by space missions (e.g., [11][12][13][14]). …”
Section: Introductionmentioning
confidence: 99%